Prevalence of under and over weight in children with neurodisability, using body composition measures. Issue 10 (October 2018) - Lip, Stefanie; Chillingworth, Anna; Wright, Charlotte
Abstract We aimed to compare rates of under and overweight in children with different neurodevelopmental disorders (NDD) by measuring weight, height/length, arm-to-leg bioelectrical impedance (BIA) and subscapular and triceps skinfolds in 146 children aged 4–16 years attending special schools. Z scores were calculated and skinfolds and lean mass Z scores were further adjusted for height. Underweight was found in 9% (14) children (body mass index (BMI) < 2nd) but only 3% (4) had skinfolds <5th centile. Overweight was much commoner, with 41% (58) children having BMI > 95th and 20% (14) had skinfolds >95th centile. Children with cerebral palsy were very short with low BMI and lean mass, but only 8% (3) had skinfolds <5th centile. The children with Down syndrome were also very short and once adjusted for height, half had skinfolds >95th centile. We conclude that overweight and raised body fat is now common in children with NDD, even when the BMI is low.